The pairwise interaction of environmental factors for ecosystem services relationships in karst ecological priority protection and key restoration areas - Liyuan Zuo (Elsevier, 2021)
Understanding the relationships among ecosystem services (ESs) and exploring their driving factors is required for the efficient eco-environment management of karst regions. This is especially so for ES hotspot/coldspot areas that would deserve priority protection/key governance. In this study, four ESs—soil conservation (SC), water yield (WY), net primary productivity (NPP), and habitat quality (HQ)—were quantified across the Wujiang Basin, a typical karst basin in China. Hotspots and coldspots of each ES were first identified through which ecological priority protection areas (EPPA) and ecological key restoration areas (EKRA) were then recognized. The objective of this study was to quantitatively identify the trade-offs and synergies and their driving factors among the karst ESs in the EPPA and EKRA. The results show that from 2000 to 2018, the distribution of ESs exhibited pronounced spatial heterogeneity in the Wujiang Basin. The EPPA were widespread in the northeast and southwest of the basin, accounting for 12.17% of its area, while the EKRA were mostly concentrated in the northwest of the basin, corresponding to 12.71% of the basin’s area. In the EKRA, evidence for a trade-off relationship was found between WY and NPP, and WY and HQ, whereas all other ES pairs had synergistic relationships in both the EPPA and EKRA. NDVI was the dominant factor explaining the spatial distribution of synergy between SC and NPP in both the EPPA and EKRA. Land use differs significantly from other factors and plays a decisive role in influencing the trade-offs and synergies of other ES pairs in the EPPA and EKRA, and it also figures prominently in the interaction with other factors. Our study provides a more mechanistically understanding of trade-offs and synergies in the EPPA and EKRA for ensuring the effective protection and management of karst ecosystem.